Characteristic MRI findings of the shoulder, elbow, and wrist joints in elite wheelchair basketball players - Masafumi Sakai; Hirotaka Mutsuzaki; Yukiyo Shimizu; Yoshikazu Okamoto; Takahito Nakajima (BMC, 2022)
Abstract Background The health of wheelchair users' upper limbs is directly related to their quality of life. Moreover, para-sport athletes are subjected to a dual load on their upper extremities from competition and daily life, making it even more critical to maintain upper extremity health. This study aimed to investigate the characteristics of joint disorders in elite wheelchair basketball players using magnetic resonance imaging (MRI). Methods We scanned MRI images of the bilateral shoulders, elbows, and wrist joints of ten elite wheelchair basketball players and ten general wheelchair users. The elite wheelchair players were athletes who underwent at our institution medical checkup of the candidates for the national team for the international women's tournament and who agreed to this research purpose. The general wheelchair players were recruited from wheelchair users in their 20s and 30s who had no daily exercise habits and who agreed to the study objectives. Two radiologists interpreted the MRI images and diagnosed the diseases of each joint. We compared the number of lesions between the two groups. We used Fisher's exact test to determine whether the lesions diagnosed by MRI were specific to wheelchair basketball players. The significance threshold was set at P < 0.05. Results Elite wheelchair basketball players had significantly more right-sided, left-sided and bilateral latero-posterior lesions, which are cysts found on the lateral-posterior corner of the capitulum of the humerus than did general wheelchair users (P < 0.05). Severe damage to the right triangular fibrocartilage complex was also observed more frequently (P < 0.05) in wheelchair basketball players. Conclusions We believe that the patients' tendency to fall forward in the wheelchair hitting both hands on the ground, thereby injuring the triangular fibrocartilage complex and locking the lateral elbow, may be the cause of the characteristic findings on MRI. High-speed wheelchair operation was also considered a cause of severe triangular fibrocartilage complex injuries. This study's insights can be useful for future solutions to extend players' careers.